Applying attachment theory to explore the emotion regulation characteristics of a child diagnosed with ADHD - Van Huyssteen, Almarie (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MEdPsych (Educational Psychology)--University of Stellenbosch, 2009.